Analysis of Economic Regulations of National Electrical Systems - Yusuf Suryanto (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2017)
The performance of the national electricity industry is inadequate. Improvements have so far ignored the highly centralized structure of the national electricity industry. Using the theory of industrial organization, comparative with developed countries, and considering the prevailing legal corridor, this paper recommends policy, in order to (i) create an un-centratious electricity system by establishing 5 electricity systems in Indonesia; (ii) continuing efforts to utilize shared networks Transmission (and distribution), and (iii) establishing the Electricity Industry Regulators. The main recommendation is to break-down the current PLN into 5 new electricity companies.